2007
DOI: 10.1111/j.1365-294x.2007.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating individual behaviour and landscape genetics: the population structure of timber rattlesnake hibernacula

Abstract: Individuals of many species show high levels of fidelity to natal populations, often due to reliance on patchily distributed habitat features. In many of these species, the negative impacts of inbreeding are mitigated through specialized behaviours such as seasonal mating dispersal. Quantifying population structure for species with these characteristics can potentially elucidate social and environmental factors that interact to affect mating behaviour and population connectivity. In the northern part of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 66 publications
2
92
0
1
Order By: Relevance
“…To date only four published studies have used genetic data to investigate sex-biased dispersal in snakes, all of which have found a male-bias (Rivera et al, 2006;Keogh et al, 2007;Clark et al, 2008;Dubey et al, 2008). Malebiased dispersal in mammalian species has been attributed to a female-defence polygyny mating system (Greenwood, 1980), and while polygyny has been regarded as typical for snakes (Duvall et al, 1993), more Smooth snake molecular ecology AP Pernetta et al recent research suggests that this may not always be the case (Rivas and Burghardt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To date only four published studies have used genetic data to investigate sex-biased dispersal in snakes, all of which have found a male-bias (Rivera et al, 2006;Keogh et al, 2007;Clark et al, 2008;Dubey et al, 2008). Malebiased dispersal in mammalian species has been attributed to a female-defence polygyny mating system (Greenwood, 1980), and while polygyny has been regarded as typical for snakes (Duvall et al, 1993), more Smooth snake molecular ecology AP Pernetta et al recent research suggests that this may not always be the case (Rivas and Burghardt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mobility of forest species is favored by wooded landscapes, and correlation coefficients between dispersal data and the LCD measures were slightly stronger than with Euclidean distance measures (see, for example, roe deer, [16]; martens, [17]; mountain vizcacha, [7]). A previous study [19] found a significant positive correlation between genetic differentiation and a cost-based distance metric adjusted to include the quantity of potential basking habitat between hibernacula.…”
Section: Discussionmentioning
confidence: 99%
“…However, most animals live in heterogeneous habitats, and individual movement is greatly influenced by landscape elements [14,15] that introduce bias into results based on a EUD measure. The least-cost path distance (LCD), which defines a measure of landscape connectivity, was, therefore, introduced as a more suitable means for assessing the inferred effects of landscape structure on gene flow [16-19]. The least-cost path avoids landscape regions that are more resistant to movement and prefers paths through permeable features.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations